The evaluation of the influence of a high injury to brachial plexus elements on the condition of neurons of the anterior horns of the spinal cord - experimental research - Knakiewicz, Monika; Rutowski, Roman; Gosk, Jerzy; Kuryszko, Jan; Kielan, Wojciech; Rudno-Rudzińska, Julia; Knakiewicz, Michał (Folia Neuropathologica, 2009)
The aim of the experimental research was to assess the impact of a high damage to brachial plexus elements on the condition of neurons of spinal cord anterior horns. The research was conducted on 12 rabbits, in which the ventral branches of spinal nerves C5-Th1 were severed. During dissections carried out 7, 30, 60, 180 days after the operation the cervicothoracic segment of the spinal cord was collected. The material was subjected to microscopic histological and ultrastructural examinations, which showed that where brachial plexus elements had been severed some of the neurons of spinal cord anterior horns had died and that the process intensity depended on the time that had passed after the injury.